Reported circulation of Zika and re-circulation of Chikungunya in Dengue-endemic Dhaka, Bangladesh in 2024 - Rahman Mizanur; Khan Fariduddin Ayaz; Hasan Nazmul; Rummana Rahim; Abu Hasan; Naoko Kawai; Tatsuki Sugi; Kyoko Hayashida; Junya Yamagishi (PLoS ONE, 2026)
Background In Dhaka, Bangladesh, dengue has been endemic for more than two decades. With the explosive outbreak of Chikungunya in 2017 and the recent report of Zika in 2023, we started routine screening of Dengue virus (DENV), Chikungunya virus (CHIKV) and Zika virus (ZIKV) of febrile patients attended in our tertiary care hospital to overcome diagnostic challenges posed by the symptomatic similarities of these viral infections. Method Serum samples of 603 febrile patients from August to December 2024 were tested by multiplex RT-PCR to detect DENV, CHIKV and ZIKV. Genome sequencing and phylogenetic analysis were performed for some of these samples. Result A total of 300 (49.8%) patients were positive for one or more viruses: 85 (14.1%) for DENV, 188 (31.18%) for CHIKV and 33 (5.47%) for ZIKV. Four CHIKV-DENV and two CHIKV-ZIKV co-infections were found. CHIKV sequences obtained in this study belonged to the ECSA clade and highly like those circulated in India from 2018 to 2024 but distinguished from Bangladesh strain of 2017. On the other hand, Bangladesh ZIKV sequences in 2024 belonged to the Asian clade and Southeast Asian subtype. They were most similar to strains circulated in Bangladesh in 2023, followed by sequences from Cambodia (2019), Thailand (2016) and Singapore (2016). Conclusion Thus, these findings underscore the need for enhanced surveillance and public health interventions to mitigate the spread and impact of these viral infections in arboviral-endemic regions.